2015
DOI: 10.1123/smej.2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Ability of Students to Engage With Theoretical Concepts Through the Creation of Learner-Generated Video Assessment

Abstract: Even though technology has become a key driver in preparing sports management students for an increasingly globalized industry, it is unclear whether the affordances of these technologies contribute to the transformation of the learning environment. The purpose of this study was to investigate how a learner-generated video assessment develops students’ critical thinking and engagement with the theoretical concepts taught in an undergraduate second-year Sociology of Sport course. Data were gathered using a qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In some studies, students recognised these skill developments as being of benefit to them beyond graduation and in their future employment ( reported that some students failed to see the relevance of the video creation project to either their education or their future careers. This is perhaps a timely reminder and demonstration of the importance of aligning skills and tasks and introducing in them in such a way as to make their relevance clear for beyond graduation above and beyond how it supports meeting immediate learning outcomes (Walters et al, 2015). (2015) reported a significant change in the pass/fail ratios when moving to video assessment, Schofield et al (2017) reported that the choice of medium for assessment between video and/ or traditional essay had no impact on student assessment outcomes.…”
Section: Ukmentioning
confidence: 96%
See 2 more Smart Citations
“…In some studies, students recognised these skill developments as being of benefit to them beyond graduation and in their future employment ( reported that some students failed to see the relevance of the video creation project to either their education or their future careers. This is perhaps a timely reminder and demonstration of the importance of aligning skills and tasks and introducing in them in such a way as to make their relevance clear for beyond graduation above and beyond how it supports meeting immediate learning outcomes (Walters et al, 2015). (2015) reported a significant change in the pass/fail ratios when moving to video assessment, Schofield et al (2017) reported that the choice of medium for assessment between video and/ or traditional essay had no impact on student assessment outcomes.…”
Section: Ukmentioning
confidence: 96%
“…The alignment of video creation for assessment to graduate capabilities required for industry is of crucial importance. Indeed, Walters et al (2015) argued that it was this alignment to graduate capabilities required for industry that students perceived as of greater value and had higher transformative potential than the innovation of video creation for assessment itself. Selwyn (2013) states that in the application of technology within educational settings it is important to consider fully how issues of local context and circumstances have an impact.…”
Section: Relevance Of Digital Capability Within Education and Beyond mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of learner-generated video to reflect on practice has been reported in a range of disciplines, including nurse education (Marita et al 1999;Pereira et al 2014), anatomical sciences (Doubleday and Wille 2014), mathematics (Borko et al 2008), surgery (Vaughn et al 2016) and sports education (Walters et al 2015). Taylor (2013) has proposed that "vlogging [video blogging] is an ideal medium for producing knowledge and sharing digital stories" precisely because it allows an informal channel where students can discuss and reflect on their own work.…”
Section: The Use Of Learner-generated Video In Higher Educationmentioning
confidence: 99%
“…Instead, it is the pedagogically focused activity created by the teacher that motivates students to use social media to complete the task. For example, in a study which examined the use of video assessment to enhance undergraduates' critical thinking, Walters, Hallas, Phelps and Ikeda (2015) found that students were not motivated to complete the assessment due to the video itself. Instead, these students perceived that while the video was fun to produce, they preferred the assessment to focus on developing an understanding of disciplinary concepts that they could apply in the workplace rather than on technical skills.…”
Section: Literature Reviewmentioning
confidence: 99%